TEACHERS’ PERSPECTIVES ON USING LITERARY TEXTS IN TEACHING ENGLISH TO EFL LEARNERS - Masintan Masintan; Ira Maisarah (JEE (Journal of English Education), 2026)
Current studies have emphasised the benefits of using literary texts in teaching English in the ESL/EFL context across all educational levels. However, little research has examined teachers’ perspectives on the implementation of literary works in their English classrooms. Therefore, this study seeks to investigate English teachers’ perspectives on the implementation of literary works in English teaching at a favourite school in Bengkulu City, Indonesia. This study adopted a descriptive qualitative method that involved three English teachers from a favourite school in Bengkulu City, Indonesia. The data were obtained by conducting semi-structured interviews. Their responses to the interviews were analysed qualitatively using an interactive model proposed by Miles and Huberman. The analysis processes included data reduction, data display, and conclusion-drawing. The results show that teachers’ perspectives on incorporating literary texts in English language teaching were positive. The literary texts could enhance students' linguistic (e.g., reading skills, vocabulary mastery, grammar accuracy) and non-linguistic competences (e.g., cultural awareness and critical thinking). However, obstacles such as students' poor language skills, time constraints, and difficulty in choosing suitable literature were also noted. Despite these obstacles, the teachers used a variety of techniques to maximise the effectiveness of literature-based instruction, such as text simplification, vocabulary pre-teaching, and interactive exercises. To conclude, when combined with suitable teaching techniques and contextual modification, literary texts have significant pedagogical potential in EFL environments.